Slavery and freedom in the Bluegrass State : revisiting My Old Kentucky Home - Smith, Gerald L., 1959- (University Press of Kentucky, 2023)
"Stephen Foster's 'My Old Kentucky Home' has been designated as the official state song and performed at the Kentucky Derby for decades. In light of the ongoing social justice movement to end racial inequality, many have questioned whether the song should be played at public events, given its inaccurate depiction of slavery in the state. In Slavery and Freedom in the Bluegrass State, editor Gerald L. Smith presents a collection of powerful essays that uncover the long-forgotten stories of pain, protest, and perseverance of African Americans in Kentucky. Using the song and the museum site of My Old Kentucky Home as a central motif, the chapters move beyond historic myths to bring into sharper focus the many nuances of Black life. Chronologically arranged, they present fresh insights on such topics as the domestic slave trade, Black Shakers, rebellion and racial violence prior to the Civil War, Reconstruction, the fortitude of Black women as they pressed for political and educational equality, the intersection of race and sports, and the controversy over a historic monument. Taken as a whole, this groundbreaking collection introduces readers to the strategies African Americans cultivated to negotiate race and place within the context of a border state. Ultimately, the book gives voice to the thoughts, desires, and sacrifices of generations of African Americans whose stories have been buried in the past"--